La metodología de enseñanza aprendizaje y su aporte al desarrollo del pensamiento nocional de los niños de 5 a 6 años en la escuela de práctica docente de la unidad educativa Calasanz, durante el período lectivo 2011-2012. Lineamientos alternativos - Córdova Jaramillo, Lisbeth Magaly; Vélez Mero, Betty del Carmen (2015)
This research had the purpose of knowing the learning methodology and its contribution to the development of notional thinking in children from 5 to 6 years old in the teaching practice school of “Unidad Educatuva Calasanz”: we investigated about the main problems of methodologies used in the teaching-learning process in the development of notional thinking in children. We used scientific methods and techniques in accordance for the design of instruments such as polls and tests to authorities, teachers and children. We obtained truthful information, which was systematized, analyzed, processed qualitatively and confronted with theoretical references. The investigation confirms to stop employing an active methodology in the teaching - learning process and the poor training in teachers, the child is limited by the absence of opportunities to develop their notional thinking therefore the inappropriate use of methodologies is affecting the development of teaching-learning process in both indoor and outdoor spaces where knowledge is generated. Behaviors such as impulsiveness, fuzzy perception, little flow ability of handling two or three sources of information, dogmatic behavior, attachment to the teacher and peers, is closely correlated with the development of thought. It has been observed as a constant of the methodology and development of thinking insecurity, difficulty in grasping the meaning of things, resistance to thinking, inability to concentrate, lack of self confidence, hard inflexible behavior. 100% of the teachers do not receive training for the development of thinking, they work with children using methods that they have gained as a result of their experience, the interest they have in research to improve their teaching practices. The lack of training limits the development of the teaching-learning process, because for lack of knowledge about which intellectual operations must develop, and which operational activities must be applied in the classroom, they cannot demonstrate the performance of the educational objectives of these children. In the final section it outlines alternatives and recommendations to teachers and administrators, in order to manage quality strategies from practical situations which could permit a significant positive relationship to provide tools that will be enriched according to its good use since the everyday life, to address the learning problems of infants, as far as it is the responsibility of schools to ensure their full development once it has registered its registration.